2023
DOI: 10.1097/corr.0000000000002629
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Are Associated With Revision Cubital Tunnel Release Within 3 Years?

Abstract: Background It has been shown that patient demographics such as age, payer factors such as insurance type, clinical characteristics such as preoperative opioid use, and disease grade but not surgical procedure are associated with revision surgery to treat cubital tunnel syndrome. However, prior studies evaluating factors associated with revision surgery after primary cubital tunnel release have been relatively small and have involved patients from a single institution or included only a single payer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In cases where the nerve is painfully dislocated, it can be treated through one of the described nerve transposition procedures [ 73 , 153 , 154 , 155 ]. A higher risk for revision surgery includes patients with workers’ compensation insurance, previous simultaneous bilateral surgery, a submuscular transposition as a primary procedure, spinal cervical disc herniation, a higher BMI, smoking and alcohol consumption, and pain problems after primary surgery, while the risk is lower among those with a higher age and a concomitant carpal tunnel release [ 153 , 156 , 157 ]. Revision surgery may result in complete or partial recovery, but residual problems, such as paresthesia, are the most frequent symptom, and patients with no improvement are common [ 155 , 158 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In cases where the nerve is painfully dislocated, it can be treated through one of the described nerve transposition procedures [ 73 , 153 , 154 , 155 ]. A higher risk for revision surgery includes patients with workers’ compensation insurance, previous simultaneous bilateral surgery, a submuscular transposition as a primary procedure, spinal cervical disc herniation, a higher BMI, smoking and alcohol consumption, and pain problems after primary surgery, while the risk is lower among those with a higher age and a concomitant carpal tunnel release [ 153 , 156 , 157 ]. Revision surgery may result in complete or partial recovery, but residual problems, such as paresthesia, are the most frequent symptom, and patients with no improvement are common [ 155 , 158 ].…”
Section: Treatmentmentioning
confidence: 99%
“…This work from Rochester (New York, USA) used big data, and aimed to determine the percentage of patients undergoing revision surgery for cubital tunnel syndrome within three years of primary cubital tunnel release. 4 The authors used the dataset to identify factors associated with the need for revision surgery. The research data were obtained from the New York Statewide Planning and Research Cooperative System database, which covers a large geographical area and includes diverse patient populations and payers.…”
Section: What Factors Are Associated With Revision Cubital Tunnel Rel...mentioning
confidence: 99%
“…Advocates of transposition cite the benefits of tension relief and relocation into a healthy tissue bed [6]. The relative efficacy of subcutaneous, intramuscular, and submuscular techniques is controversial, with submuscular potentially offering more "protection," but also a greater potential for perineural scarring [11]-a concern potentially borne out by the findings reported by Schloemann et al [9] in this issue of Clinical Orthopaedics and Related Research ® . In situ release is simpler and quicker, preserving the natural blood supply to the nerve [5], and with endoscopic-assisted techniques or with firm retraction, an extensive release can be performed through a small incision.…”
mentioning
confidence: 99%
“…As highlighted in this month's CORR ® , Schloemann et al [9] found that factors affecting the likelihood of undergoing revision cubital tunnel surgery seem to extend beyond the success or failure of the index procedure and must also reflect the patient's eagerness for further treatment, the surgeon's perception that something may have gone wrong with the index procedure, or the surgeon's reluctance to perform additional procedures. For example, patients with workers compensation (secondary gain) and patients who underwent submuscular transposition (a more complex and therefore riskier procedure) were more likely to receive revision surgery, while patients with comorbidities (higher potential for medical complications) were less likely to [9].…”
mentioning
confidence: 99%